A molecular and morphological characterization of Oliver’s parrot snake, Leptophis coeruleodorsus (Squamata: Serpentes: Colubridae) with the description of a new species from Tobago - Murphy, John C.; Charles, Stevland P.; Lehtinen, Richard M.; Koeller, Krista L. (Zootaxa, 2013)
Currently, two snake species of the genus Leptophis occur in Trinidad and Tobago. One, L. stimsoni, is endemic to Trinidad’s Northern Range and known from relatively few specimens. The second is the diurnal, arboreal, brightly colored parrot snake Leptophis coeruleodorsus Oliver. It was originally described based on 23 specimens from Trinidad, Tobago, and four locations in northern Venezuela but remains poorly known. It was later assigned as a subspecies of Leptophis ahaetulla; a widespread, polytypic species. Here we compare 11 specimens of the L. ahaetulla Group using DNA sequences from two mitochondrial genes (cytochrome b and 16S, 1,383 bp total) from island and mainland populations, report on the variation in the morphology of 54 museum specimens of Leptophis a. coeruleodorsus; describe the previously undescribed holotype of L. coeruleodorsus Oliver, and restrict its type locality. Additionally, we describe a new species of Leptophis from the island of Tobago that can be distinguished from L. coeruleodorsus on the basis of snout shape, upper labial architecture, elongated prefrontal scales, and ventral scale counts. The new Leptophis raises the number of endemic Tobago amphibians and reptiles to 11 taxa.